2000
DOI: 10.1053/eupc.2000.0103
|View full text |Cite
|
Sign up to set email alerts
|

Latest generation of unipolar and bipolar steroid eluting leads Long-term comparison of electrical performance in atrium and ventricles

Abstract: One hundred and seventy-three patients, mean age 74 years permanently paced with 123 atrial (53 unipolar, 70 bipolar) and 143 ventricular (73 unipolar, 70 bipolar) pacing leads were included in this study. The pacing leads were recent generation low surface area steroid eluting leads from one manufacturer: leads with silicone and polyurethane insulation were studied, and they were combined with generations of one pacemaker family from the same manufacturer permitting identical measurements to be made over a fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Electrical performances were within ranges retrieved in the literature for the atrium: PCT was comparable to values observed by Kistler et al [9], P-wave amplitude were close to those reported by Rickard [6] and Cornacchia [10], and impedance values compared to those found by Kistler [9] and Lotze et al [11]. In the ventricle, PCT values compared with those reported by Rickard [6] and Lotze et al [11]; sensing amplitude were aligned with Nagatomo et al [12] and Schuchert et al [13].…”
Section: Discussionsupporting
confidence: 89%
“…Electrical performances were within ranges retrieved in the literature for the atrium: PCT was comparable to values observed by Kistler et al [9], P-wave amplitude were close to those reported by Rickard [6] and Cornacchia [10], and impedance values compared to those found by Kistler [9] and Lotze et al [11]. In the ventricle, PCT values compared with those reported by Rickard [6] and Lotze et al [11]; sensing amplitude were aligned with Nagatomo et al [12] and Schuchert et al [13].…”
Section: Discussionsupporting
confidence: 89%
“…Whereas, in the bipolar lead, there is a separate lead between sensing lead and pacing lead. Bipolar lead more superior in eliminating oversense noncardiac signal (Cornacchia et al, 2000). In the Unipolar lead system, the metal part of the pacemaker's generator serves as an anode (positive pole) and lead as a cathode (negative pole).…”
Section: Pacing Leadsmentioning
confidence: 99%
“…In few cases, the unipolar lead's sensing and capture thresholds might be superior to bipolar lead (Cornacchia et al, 2000). To overcome unipolar lead's problem in over-sense pectoral myopotential, protective coating on the device might contribute in this case.…”
Section: Pacing Leadsmentioning
confidence: 99%